2003
DOI: 10.1124/jpet.103.052324
|View full text |Cite
|
Sign up to set email alerts
|

Steroids ModulateN-Methyl-D-aspartate-Stimulated [3H]Dopamine Release from Rat Striatum via σ Receptors

Abstract: Steroids have been proposed as endogenous ligands at receptors. In the current study, we examined the ability of steroids to regulate N-methyl-D-aspartate (NMDA)-stimulated [ 3 H]dopamine release from slices of rat striatal tissue. We found that both progesterone and pregnenolone inhibit [ ,7,8,9,10, (LY379196) against both progesterone and pregnenolone. We found that LY379196 at 30 nM reversed the inhibition of release by both progesterone and pregnenolone. These findings support steroids as candidates for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Relatively high levels of PROG, and its derivatives, DHP and THP, have been previously detected in the human SNc and caudate nucleus, with respect to other brain areas (Bixo et al 1997), suggesting that substantial synthesis and accumulation of neuroactive steroids may take place in the nigrostriatal system. Various studies have also reported that neuroactive steroids can affect synaptic transmission at the cortico-striatal level, by modulating the striatal release of dopamine (Nuwayhid and Werling 2003;Sadri-Vakili et al 2008;Whittaker et al 2008). Moreover, neuroactive steroids can act as either positive or negative modulators of the GABA-A receptor (Belelli and Lambert 2005); this class of molecules may, therefore, intervene in the modulation of basal ganglia circuitry activity, where GABAergic transmission plays a crucial role at various sites (Blandini et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Relatively high levels of PROG, and its derivatives, DHP and THP, have been previously detected in the human SNc and caudate nucleus, with respect to other brain areas (Bixo et al 1997), suggesting that substantial synthesis and accumulation of neuroactive steroids may take place in the nigrostriatal system. Various studies have also reported that neuroactive steroids can affect synaptic transmission at the cortico-striatal level, by modulating the striatal release of dopamine (Nuwayhid and Werling 2003;Sadri-Vakili et al 2008;Whittaker et al 2008). Moreover, neuroactive steroids can act as either positive or negative modulators of the GABA-A receptor (Belelli and Lambert 2005); this class of molecules may, therefore, intervene in the modulation of basal ganglia circuitry activity, where GABAergic transmission plays a crucial role at various sites (Blandini et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Neurosteroid interactions at sigma-receptors have been reported to either positively or negatively modulate NMDARmediated responses in CNS (Hayashi et al, 1995;Monnet et al, 1995;Debonnel et al, 1996a,b;Nuwayhid and Werling, 2003;Bermack and Debonnel, 2005). Therefore, it was important to determine that blockade of sigma-receptors by BD1047 did not modulate NMDAR-dependent LTP induced by 100 Hz stimulation at CA1 synapses.…”
Section: Involvement Of Sigma-receptors In Pregs Facilitation Of Nmdamentioning
confidence: 97%
“…[93][94][95][96] Sigma receptors regulate the release of neurotransmitters, 6,97 and are thought to do so by modulating calcium influx and intracellular calcium mobilization, and by acting upon PKC pathways. 6,95 It is hypothesized that selective sigma ligands mediate neuroprotection by indirectly inhibiting ischemicinduced presynaptic glutamate release. 10 The reduction of glutamate release by DM 9 may therefore relate to a sigmarelated inhibition of VGCC-dependent synaptic release.…”
Section: Werling Et Almentioning
confidence: 99%